The Use of Content Analysis to Assess Letterland Book for Kindergarten Students - Ariyani, Nindya Putri; Faridi, Abdurrahman; Rozi, Fahrur (Universitas Negeri Semarang, 2021)
Most of previous researches investigated the use of Letterland method in teaching English. However, only few researches concern with the Letterland book that have many differences with local story books in Indonesia. This research was aimed to find out how the quality of Letterland book refers to listening, reading, and vocabulary skills, language content (topic, subject content and social and culture values) and the effectiveness of Letterland book. Content analysis method was applied in this research. There were two instruments which are used in this reseach, they are : document and interview that involved teachers in Star Kiddy Preschool and Learning Center. This research used Cunningsworth theory as guidance to analyse the quality of Letterland book. The findings showed that listening, reading, vocabulary skills in Letterland book are categorized as good book. The language contents of Letterland book is qualified as good EFL book criteria. Teachers in Star Kiddy Preschool Star Kiddy Preschool and Learning Center stated that Letterland book is effective to learn English for children. However, there were problems in the implementation of Letterland book such as: limited time, new teachers that had not expert on Letterland book. Therefore, this research was expected to be the an overview of teachers that learnt English by using Letterland book for children.